A comparative study of the impact of Korean research articles in four academic fields using altmetrics. Issue 1 (10th April 2017) - Cho, Jane
Abstract : Purpose: Alternative metrics (altmetrics) are non-traditional metrics to measure the social impact of research results, which were unable to be assessed by the previous methods, by calculating how research results are reflected in various social media. The purpose of this paper is to measure and compare the impact of Korean study results in four fields that were published in international journals using altmetrics. Design/methodology/approach: This study analysed the impact of 383 Korean research articles published by international journals in the field of medical science, engineering, social science and arts and humanities through altmetrics and compared it with bibliometrics. Findings: As a result, the frequency of research articles which are "discussed" through social media such as Twitter was shown to be highest in the medical science than in other fields. In addition, the frequency of research articles which were "saved" through reference management tool such as Mendeley was shown to be higher in the social science and the arts and humanities than in other fields. Furthermore, as a result of a correlation analysis between altmetrics and bibliometrics, it is found that there exists a positive correlation between the number of articles which were "saved" in Mendeley and "cited" in follow-up studies. Originality/value: This study examined the impact of the articles originating in non-English-speaking nations; it could be referred by other non-English-speaking nations that are trying to identify invisible impact of their research output on global society. By finding the academic field which are receiving special attention from global community using altmetrics, researchers could prospect country's overall research impact and utilize it to make a future R&D plan.